Trajectory Planning of a 6-DOF Assembly Robot Based on the Atomic Orbit Search Algorithm - Huang Deqi; Wu Jianhui (Jixie chuandong)
Aiming at the multi-objective optimization and trajectory planning problems of six-degree-of-freedom assembly robots, firstly, the atomic orbit search (AOS) algorithm is incorporated into the multi-objective optimization to construct the multi-objective optimization functions of time, energy consumption and shock. Secondly, the trajectory planning adopts the method of path point interpolation non-uniform rational B-spline curve, uses the AOS algorithm to determine the binding state and the binding energy of atoms, determines the candidate solution with the lowest energy level in the atom, outputs the optimal electron position, optimizes the Pareto value set space, and obtains the multi-objective optimized trajectory curve. Finally, the effectiveness of the proposed method is verified by the Matlab simulation. The results show that the trajectory planning method combined with the AOS algorithm can ensure that the assembly robot runs in the optimal route, which has certain engineering application value.